Learning Motivation as a Predictor of Creativity in Fifth Grade Elementary School Students - Handayani, Retno Dwi; Subiyantoro, Slamet; Chumdari, Chumdari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Creativity plays a crucial role for students because it provides various benefits that support their overall development, both in academic and personal aspects. This study aims to: 1) determine the learning motivation of fifth-grade elementary school students, 2) determine the creativity of fifth-grade elementary school students, and 3) determine the influence of learning motivation on the creativity of fifth-grade elementary school students. This research method uses a quantitative method with an ex-post facto design. Data collection was carried out through a learning motivation questionnaire and creativity observation sheet. The questionnaire instrument is used to obtain data on students' learning motivation. Observation sheets are used to determine students' creativity. Data were collected through a learning motivation questionnaire and a creativity observation sheet. Data analysis techniques consist of prerequisite tests and hypothesis tests. The prerequisite tests consist of normality tests and homogeneity tests. Hypothesis testing uses a t-test with the help of the IBM SPSS Statistics 22 program. The results of this study indicate the influence of learning motivation on the creativity of fifth-grade elementary school students in batik making with a p-value of 0.000 < 0.05. The conclusion of this study confirms that learning motivation has a significant influence on the creativity of fifth-grade elementary school students.